A new species of myxozoa in the skeletal striated musculature of Rhamdia quelen (Quoy & Gaimard) (Siluriforme: Pimelodidae) Amazonian fish, Marajó island, Brazil - Abrunhosa, Jacqueline; Sindeaux-Neto, Jose L.; Santos, Sidney; Hamoy, Igor; Matos, Edilson (Zootaxa, 2018)
A new myxozoan was found parasitizing the freshwater catfish, Rhamdia quelen (Quoy & Gaimard), in the Marajó island, Amazon region, Brazil. The new species is described based on the results of morphological and molecular analyses. The parasite is approximately 1.5 mm in diameter and develops in the musculature of the host in the form of spherical, whitish cysts, which are visible macroscopically between the epaxial and hypaxial layers. When ruptured, these cysts produced ellipsoidal spores with a mean length of 11.4 μm (10.7–12.6) and width of 7.2 μm (6.4–7.9). Anomalous spores with a caudal elongation, vesicles in the peripheral portion of the spore and ornamentation of the valves were also observed. The results of the phylogenetic analysis of sequences of the 18S rDNA gene using Bayesian Inference indicated clear differences among the Myxobolus species that reinforced the taxonomic position of the parasite, confirming its status as a new species, denominated Myxobolus arariensis n. sp.